Investigating the Influence of Cosmic Rays on Ozone Layer Depletion at Beijing, China - Bulbul Jan; M. Ayub Khan Yousuf Zai (Journal of Basic & Applied Sciences, 2021)
In the present study monthly and annually data of ozone depth and cosmic rays (CRs) intensity at China Beijing during the period of 1984-2010 have been analyzed to investigate the effects of cosmic rays intensity on ozone layer depletion (OLD). This communication implements statistical analysis on the data sets for the specified period mentioned above. The analyses exhibit that mean monthly variation of cosmic rays intensity increases. Our investigation claims that in the month of May (1984-2010) changes occurred in the decrease the ozone depth due to the increase in cosmic rays intensity .This sort of study confirms cosmic rays influence on the ozone layer depletion.